Ambient temperature and field-based cycling performance: Insights from male and female professional cyclists - Valenzuela, P. L.; Mateo-March, M.; Zabala, M.; Muriel, X.; Lucia, A.; Barranco-Gil, D.; Pallarés, J. G. (International Journal of Sports Physiology and Performance, 2022)
Purpose: Ambient temperature affects endurance exercise performance. However, most research has been conducted in a laboratory-based setting, and whether there are sex-specific trends remains unclear. The present study aimed to analyze the influence of ambient temperature on cycling performance in male and female professional cyclists using field-based data collected during both training and racing. Methods: A total of 74 cyclists (48 male and 26 female; age 29 [5] y, 8 [5] y of experience in the professional category) were included in the analyses. We registered the participants` record power profile using data from both training and competitions over 8 years (2013-2020; 8 [5] seasons per cyclist). We analyzed their mean maximal power (MMP) values attained for efforts lasting 5 seconds, 30 seconds, 5 minutes, and 20 minutes at ambient temperatures ranging from <5°C to >35°C. Results: A significant influence of ambient temperature on MMP values was found in male and female cyclists (P < .001 for both), with no significant differences between sexes (P = .512). Cyclists attained the highest MMP values at temperate conditions (10-30°C in males and 5-25°C in females), whereas an impairment in performance was found at colder and hotter temperatures, particularly for the more extreme conditions (performance impairment at <5°C and >35°C of -18% to -9% and -16% to -9%, respectively). Conclusions: Ambient temperature influences field-based cycling performance, following a reverse U-shaped relationship, with the highest MMP values attained in the range of ~10°C to 25°C and with no major differences between sexes.